2021
DOI: 10.1086/712783
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Assessment of Ex Situ Collections of EndangeredQuercus hinckleyi

Abstract: Premise of research. Conservation of imperiled plant species can benefit from ex situ collections, including the living collections of botanic gardens and arboreta. Such living collections should strive to capture and maintain the genetic diversity found in the remaining wild populations. Ex situ collections may also harbor genetic variability that has been lost from wild populations. Quercus hinckleyi is an extremely rare (International Union for Conservation of Nature and Natural Resources [IUCN] Critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Quercus hinckleyi is a Critically Endangered species with an extremely limited distribution in Texas, USA. Population genetic studies have examined clonality, diversity and population structure [18], hybridization [55], and genetic diversity assessment of in situ and ex situ populations [54]. Important for conservation, Backs et al [18] reported a high level of clonality at some sites, with the number of genetically unique individuals being substantially lower than previously assumed from population counts.…”
Section: Population Genetics For Oaks Of Concernmentioning
confidence: 99%
See 2 more Smart Citations
“…Quercus hinckleyi is a Critically Endangered species with an extremely limited distribution in Texas, USA. Population genetic studies have examined clonality, diversity and population structure [18], hybridization [55], and genetic diversity assessment of in situ and ex situ populations [54]. Important for conservation, Backs et al [18] reported a high level of clonality at some sites, with the number of genetically unique individuals being substantially lower than previously assumed from population counts.…”
Section: Population Genetics For Oaks Of Concernmentioning
confidence: 99%
“…Desiccation is part of the standard protocol of conventional seed-banking [101][102][103][104]. Conservation of living oaks in ex situ collections can be constrained by space limitations, long generation times, and their proclivity to hybridize [54]. A recent paper by Backs et al [54] reported that ex situ collections of Q. hinckleyi were likely sampled from only one of the remaining in situ genetic clusters and missed much of the in situ diversity.…”
Section: Population Genetics For Oaks Of Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…A strategy that has proven especially useful for the conservation of very rare plant species is to utilize ex situ collections where specimens are grown in conservation collections and stored in seed banks (Backs et al, 2021; Foster et al, 2022; Wolkis et al, 2021). However, a major challenge for ex situ collections is a lack of information about wild source populations as well as capturing the genetic variation of their origin (Backs et al, 2021; Maunder et al, 2001). Previous studies provide examples of critically endangered Hawaiian endemic plants, such as Brighamia insignis A.…”
Section: Introductionmentioning
confidence: 99%